Prevailing Housing and Healthcare Management Practices in Urban and Peri-Urban Dairy Farms of Navsari District, Gujarat State - Rathva, AL; Sorathiya, LM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Personal interviews collected the required information from a total of 40 dairy farms from urban and peri-urban areas in and aroundNavsari. Frequency distribution was made from collected data, and significance between two categories was tested by the Chi-squaretest. Data revealed that all farms provided housing round the year. The majority of the sheds had cement type of pillars and pucca floor.Gabled roof was more popular in peri-urban areas. The majority of the farms had animal shed away from human dwelling, east-westdirectional, a double row with head to head. The majority of the sheds had adequate light and good ventilation with drainage facilityand manure pit located at an adjacent distance. The majority of farms (90%) practiced regular vaccination to their animals against footand mouth disease and hemorrhagic Septicaemia disease. The majority (82.5%) of the respondents practiced deworming of their dairyanimals regularly and also followed practices to control ectoparasites. However, only 37.5% of the farmers got their sick animals treatedby veterinary officers, and 40% of farmers segregate disease affected animals. The study concluded that the majority of the farmersfollowed housing and health care management practices for improving the production potential and health of the dairy animals.
Keywords: : Dairy farms; Healthcare; Housing; Management Practices; Peri-urban; Urban